Architectural drawing & planning - Goodban, William T.; Hayslett, Jack J. (New York : McGraw Hill Education, 1965)
This text presents the basic subject matter, order of development, and drafting techniques of architectural drawing. The goal is to develop drafting, not design ability; however, material on simple planning procedures is included to make the overall development of a set of drawings clear. The material is limited to residential and light-commercial construction.
Preface -- Note to the user -- 1. Basic skills and terminology -- 2. Lettering -- 3. Residential planning -- 4. Planning light-commercial buildings -- 5. Mechanical steps in planning -- 6. Orientation -- 7. Landscaping -- 8. Regional differences in design and construction -- 9. Presentation drawings -- 10. Working drawings -- 11. Relationships among drawings -- 12. Floor plan -- 13. Door, window, and room-finish schedules -- 14. Structural sections -- 15. Stair and fireplace details -- 16. Exterior elevations -- 17. Foundation plan -- 18. Roof and floor framing plans -- 19. Electrical plan -- 20. Heating, ventilating, and air-conditioning plan -- 21. Plumbing plan -- 22. Plot and landscaping plans -- 23. Interior elevations -- 24. Door and window details -- 25. Miscellaneous details -- 26. Specifications -- Appendix -- Bibliography -- Answers to review questions -- Index.
Includes bibliographical references and index.
Keywords: ARCHITECTURAL DRAWING